Welding and metal fabrication - Jeffus, Larry F. (Delmar, Cengage Learning, 2012)
A welding and metalwork textbook combines the skills of measuring, cutting, shaping, fitting, welding, and finishing and includes hands-on exercises, experiments, and projects.